Wireless Sensor Network Based Fault Diagnosis Approaches - Yaman, Orhan; Aydin, Ilhan; Karakose, Mehmet; Akin, Erhan (Ieee, 2013)
The development of a monitoring system for critical components is rather important to accurately detect different defects in incipient stage. Induction motors are the workhorses of many industrial systems. Fault occurred in this motor has severe effects such as cost, safety, and production disruption. In this study, a wireless sensor network-based fault diagnosis system is proposed for bearing and stator faults occurred in induction motors. The fault related features are extracted from current signal of the motor and the faults are detected by using the obtained features with intelligent computing techniques. In the established laboratory environment, conditions of multiple motors are monitored by obtaining signals from wireless sensor nodes. All steps of the proposed approach such as data acquisition, signal processing, and decision making have been experimentally carried out and verified.
Kablosuz duyarga a? tabanli ariza teşhis yaklaşimlar
21st Signal Processing and Communications Applications Conference (SIU) -- APR 24-26, 2013 -- CYPRUS
Keywords: Wireless sensor networks; induction motors; fault detection; principal component analysis; fuzzy logic